Association between ultrasound quadriceps muscle status with premorbid functional status and 60-day mortality in mechanically ventilated critically ill patient: a single-center prospective observational study - Lee, Zheng Yii; Ong, Su Ping; Ching, Choe Ng; Sing, Cindy Ling Yap; Patrick Engkasan, Julia; Mohd Yusof, Barakatun Nisak; Heyland, Daren K.; Hasan, M. Shahnaz (Elsevier, 2021)
Background & aims: In critically ill patients, direct measurement of skeletal muscle using bedside ultrasound (US) may identify a patient population that might benefit more from optimal nutrition practices. When US is not available, survey measures of nutrition risk and functional status that are associated with muscle status may be used to identify patients with low muscularity. This study aims to determine the association between baseline and changing ultrasound quadriceps muscle status with premorbid functional status and 60-day mortality. Methods: This single-center prospective observational study was conducted in a general ICU. Mechanically ventilated critically ill adult patients (age ≥18 years) without pre-existing systemic neuromuscular diseases and expected to stay for ≥96 h in the ICU were included. US measurements were performed within 48 h of ICU admission (baseline), at day 7, day 14 of ICU stay and at ICU discharge (if stay >14 days). Quadriceps muscle layer thickness (QMLT), rectus femoris cross sectional area (RFCSA), vastus intermedius pennation angle (PA) and fascicle length (FL), and rectus femoris echogenicity (mean and standard deviation [SD]) were measured. Patients' next-of-kin were interviewed by using established questionnaires for their pre-hospitalization nutritional risk (nutrition risk screening-2002) and functional status (SARC-F, clinical frailty scale [CFS], Katz activities of daily living [ADL] and Lawton Instrumental ADL). Results: Ninety patients were recruited. A total of 86, 53, 24 and 10 US measures were analyzed, which were performed at a median of 1, 7, 14 and 22 days from ICU admission, respectively. QMLT, RFCSA and PA reduced significantly over time. The overall trend of change of FL was not significant. The only independent predictor of 60-day mortality was the change of QMLT from baseline to day 7 (adjusted odds ratio 0.95 for every 1% less QMLT loss, 95% confidence interval 0.91-0.99; p = 0.02). Baseline measures of high nutrition risk (modified nutrition risk in critically ill ≥5), sarcopenia (SARC-F ≥4) and frailty (CFS ≥5) were associated with lower baseline QMLT, RFCSA and PA and higher 60-day mortality. Conclusions: Every 1% loss of QMLT over the first week of critical illness was associated with 5% higher odds of 60-day mortality. SARC-F, CFS and mNUTRIC are associated with quadriceps muscle status and 60-day mortality and may serve as a potential simple and indirect measures of premorbid muscle status at ICU admission.